Mastering blockchain - Lantz, Lorne; Cawrey, Daniel (Ascent Audio, 2022)
The future will be increasingly distributed. As the publicity surrounding Bitcoin and blockchain has shown, distributed technology and business models are gaining popularity. Yet the disruptive potential of this technology is often obscured by hype and misconception. This detailed guide distills the complex, fast moving ideas behind blockchain into an easily digestible reference manual, showing what's really going on under the hood. Finance and technology pros will learn how a blockchain works as they explore the evolution and current state of the technology, including the functions of cryptocurrencies and smart contracts. This book is for anyone evaluating whether to invest time in the cryptocurrency and blockchain industry. Go beyond buzzwords and see what the technology really has to offer. In this book, you'll learn why Bitcoin was fundamentally important in blockchain's birth; how Ethereum has created a fertile ground for new innovations like Decentralized Finance, Non-Fungible Tokens, and Flash Loans; how cryptocurrencies are used by criminals to carry out nefarious activities; and how enterprise and governments are leveraging the blockchain. You'll also discover the challenges of scaling and forking a blockchain; find out how different blockchains work; and learn the language of blockchain as industry terms are explained.